Academic Theology Centered on Practical Theology. (December 2014) - Iversen, Hans Raun
Abstract This article argues that there are considerable advantages for society, university, theology and the church to conduct theological research and education of pastors at a secular state university like the University of Copenhagen. The disadvantage is foremost that learning from a practice‐theory‐practice model is not found in theological education at the secular university. In the case of Denmark, this is, however, more due to the theology and set up of the church than to the university, where it is commonplace to integrate practice in academic studies.